Clinical importance of the expression of CD4+CD8+ T cells in renal cell carcinoma. (17th January 2020) - Nishida, Kentaro; Kawashima, Atsunari; Kanazawa, Takayuki; Kidani, Yujiro; Yoshida, Tetsuya; Hirata, Michinari; Yamamoto, Kei; Yamamoto, Yoko; Sawada, Masaaki; Kato, Ryo; Kato, Taigo; Hatano, Koji; et al.
Abstract : CD4 + CD8 + T cells are a prognostic marker for renal cell carcinoma Abstract: Objective: CD4 + CD8 + T cells are expressed in some cancer patients including those with renal cell carcinoma (RCC). However, no reports have mentioned the clinical importance of this expression. We evaluated the expression of CD4 + CD8 + T cells in patients with various cancer types to clarify clinical characteristics and prognostic importance significantly correlating with these T cells. Methods: Expression of CD4 + CD8 + T cells was evaluated using flowcytometry in tissue-infiltrating lymphocytes extracted from 260 cancer tissues including 104 RCC samples. RNA sequencing and characterization and regression (Citrus) was used to determine characteristics. The prognostic importance of CD4 + CD8 + T cells was evaluated by Cox regression analysis. Results: Among eight cancer types, expression of CD4 + CD8 + T cells was significantly highest in RCC patients. According to the expression of CD4 + CD8 + T cells in adjacent normal tissue-infiltrating lymphocytes, 24 patients (23.1%) were defined as being positive for CD4 + CD8 + with an expression higher than 9.29% in RCC patients. Citrus showed CD8 + PD-1 + TIM-3 + CD103 − T cells to be a specific subpopulation of CD4 + CD8 + T cells. RNA sequencing revealed that CD4 + CD8 + T cells had significantly lower diversity than the other T cells and shared most T-cell receptor clones with CD8 + not CD4 + T cells. Expression of CD4 + CD8 + T cells was identified as an independent predictor of overall survival (hazard ratio: 0.11, 95% confidence interval: 0.01–0.86, P = 0.035) in multivariate analysis. Conclusions: The expression of CD4 + CD8 + T cells was significantly up-regulated in RCC patients and correlated significantly with prognostic importance in surgically treated RCC patients.